New Epidemiological, Clinical and Economic Data for Patients With Acromegaly in Bulgaria - Kamusheva, Maria; Vandeva, Silvia; Mitov, Konstantin; Rusenova, Yanitsa; Elenkova, Atanaska; Zacharieva, Sabina; Mitkova, Zornitsa; Tachkov, Konstantin; Dimitrova, Maria; Doneva, Miglena; Tcharaktchiev, Dimitar; Petrova, Guenka (Frontiers in Public Health, 2020)
Background: Acromegaly and its comorbidities affect the patients’ quality of life, each healthcare system and the society. This study aimed to evaluate clinical characteristics and treatment patterns and the economic burden of acromegaly. Materials and methods: All patients with acromegaly treated with expensive medicines and regularly followed up at the main expert clinical center for acromegaly in the country were included in this nationwide, retrospective, observational, population-based study. Patient characteristics, treatment patterns, healthcare resource use, and costs were assessed for 1-year period (01.01.2018 – 31.12.2018). Results were processed through statistical analysis using MedCalc software version 16.4.1. Results: A total of 191 acromegaly patients were observed. Approximately 67% were female, 45.5% were between 41 and 60 years and the mean age at diagnosis was 40.73 years. Surgical treatment was preferred as a first-line therapy among almost 89% of all diagnosed patients. The level of comorbidities was very high as more than 95% suffered from at least one concomitant disease. The most frequent comorbidities were other endocrine and metabolic diseases (96.7%), followed by cardiovascular diseases (70.7%). The most common first-line pharmacotherapy was long-acting somatostatin analogues (SSA) (38%) followed by dual combination SSA + pegvisomant (21%). The total economic burden of acromegaly was estimated to be 2,674,499.90 € in 2018 as the direct costs (medication costs, hospitalization costs covered by the patients and the National Health Insurance Fund) outnumbered indirect costs (loss of productivity due to hospitalization): 2,630,568.58 € vs. 43,931.32 €. The average annual per-patient direct and indirect costs were 14,002.62 €. Conclusions: The current study demonstrates a significant clinical and socio-economic burden of acromegaly in the country. Proper diagnosing and regular follow up of acromegaly patients in a specialized pituitary center ensure appropriate innovative pharmacotherapy with achievement of disease control.